Geographic Distribution of Common and Dwarf Bunt Resistance in Landraces of Triticum aestivum subsp. aestivum - Bonman, J. Michael; Bockelman, Harold E.; Goates, Blair J.; Obert, Don E.; McGuire, Patrick E.; Qualset, Calvin O.; Hijmans, Robert J. (Wiley, 2006)
Landrace accessions of wheat (Triticum aestivum L. subsp. aestivum) from the USDA‐ARS National Small Grains Collection (NSGC) have been tested systematically for the past 25 yr for disease resistance. We analyzed the resistance of 10 759 common wheat accessions to common bunt (CB) caused by Tilletia tritici (Bjerk.) Wint. and T. laevis Kühn, and 8167 to dwarf bunt (DB) caused by T. controversa Kühn with respect to geographic origin, relationship to color of awn, glume, and kernel of accessions, and phenotypic variation within areas of high frequency of resistance. A clear center of concentration was evident for CB resistance extending from Serbia and Montenegro through Macedonia, Turkey, and Iran with the highest frequency of resistance occurring in Kosovo province in Serbia and Montenegro (36%) and Bakhtaran province in Iran (40.8%). Compared to CB resistance (5.5% of total tested), DB resistance was more rare (1.3% of total tested). DB resistance was concentrated in accessions from Iran, Turkey, and Serbia and Montenegro with the highest frequency (58%) occurring in Hakkari province in southeastern Turkey. CB resistance was positively associated with lightly pigmented kernels and negatively associated with lightly pigmented awns and glumes. Analysis of accessions from areas with unusually high frequency of resistance suggested that DB resistant accessions from Hakkari are genetically diverse, whereas CB resistant accessions from Bakhtaran may be much less so.